A manufacturing framework for capability-based product-service systems design - Annamalai Vasantha Gokula Vijaykumar; Hitoshi Komoto; Romana Hussain; Rajkumar Roy; Tetsuo Tomiyama; Steve Evans; Ashutosh Tiwari; Stewart Williams (Journal of Remanufacturing, 2013)
Manufacturers aim to design product-service systems (PSS) which integrate services with products to attain sustained competitive advantage from a life cycle perspective. PSS design should be customised solutions which are aligned to integrated stakeholders' capabilities, a subject which the extant literature has not sufficiently addressed. This paper proposes a systematic framework for the PSS solution provider to address this aim and operationalizes this through software developed for PSS design which models stakeholders' individual activities and simulates their occurrences depending on their relations. The framework stresses that integrated stakeholders' capabilities define continuing ability to generate a desired operational outcome for the customers. The paper reports a PSS design case for a laser system manufacturer and then applies the framework to it. The industrial experts' views on this framework reveal that it helps to develop PSS design from a holistic systems approach which facilitates a change in the designer's mindset from a product-centric to a systems-centric. The level of trust and transparency required for this framework is argued to be absent in most industrial sectors, being one of the foremost limitations for implementation of PSS.
Keywords: 650; Product-service system; Design; Framework; Simulation; Representation